2019
DOI: 10.1039/c9lc00173e
|View full text |Cite
|
Sign up to set email alerts
|

Traction microscopy with integrated microfluidics: responses of the multi-cellular island to gradients of HGF

Abstract: Microfluidic system integrated with cell collectives and traction microscopy demonstrates that collective cell migration plays a central role in development, regeneration, and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Since observation of the dynamics of these cell clusters is limited using conventional biological methods, biophysical methods, such as TFM, have allowed the mechanisms of collective cell behavior to be studied and more clearly understood [ 33 ]. In this study, in order to quantify the dynamics of the movement and physical force of collective cells under a fluid flow environment, a traction force-measurable microfluidic chip was developed by improving upon the system developed in our previous study [ 28 ]. The microchannel in the inlet and outlet was designed in the shape of a tree branch such that a constant flow rate was evenly distributed over the cell islands arranged in the channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since observation of the dynamics of these cell clusters is limited using conventional biological methods, biophysical methods, such as TFM, have allowed the mechanisms of collective cell behavior to be studied and more clearly understood [ 33 ]. In this study, in order to quantify the dynamics of the movement and physical force of collective cells under a fluid flow environment, a traction force-measurable microfluidic chip was developed by improving upon the system developed in our previous study [ 28 ]. The microchannel in the inlet and outlet was designed in the shape of a tree branch such that a constant flow rate was evenly distributed over the cell islands arranged in the channel.…”
Section: Discussionmentioning
confidence: 99%
“…Phase contrast cell and fluorescent bead images obtained by time-lapse microscopy were computed to quantify cellular motility and force using the customized MATLAB code used in previous studies [ 27 , 28 ]. Briefly, at each time point, the cell image and its next cell image or bead image and the reference bead image were calculated using a particle image velocimetry (PIV) algorithm based on cross-correlation (calculation of correlation between serial cell images).…”
Section: Methodsmentioning
confidence: 99%
“…The acquired bright-field cell images were numerically transformed and quantitatively analyzed using custom codes written in MATLAB (MathWorks Inc., Portola Valley, CA, USA). The codes used in this study to extract cell displacements and velocities are based on the particle image velocimetry (PIV) code used in the previous study [ 24 , 25 ]. The consecutive cell island images of 1216 × 1216 pixels (1070 × 1070 μm) taken at 10 min intervals were cross-correlated using unit pixel subset windows (interrogation windows, IWs) of 64 × 64 pixels at a spacing of 16 pixels (14 μm).…”
Section: Methodsmentioning
confidence: 99%
“…Especially, the free edge migration model using a micro-sized stencil is a simple and ideal tool to investigate the collective cell migration [ 23 , 24 ]. Analysis of cellular kinematics and force distribution based on patterning technology showed that cell-cell junction such as cadherin and redistribution of vinculin is important to control the collective cell migration [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, these methodologies, broadly referred to as traction force microscopy (TFM), continue to yield insightful biological trends linking cell‐generated forces to biological phenomena (Figure 2). [ 141,156–158 ]…”
Section: Measuring Cell and Tissue Mechanical Properties For Mechanotmentioning
confidence: 99%